Cases of cow reproductive disorders at The Northern Bandung Dairy Farmer Cooperative by using Geographic Information System (GIS) approach - Triyatjaya, Yoga; Solihati, Nurcholidah; Septiyani, Septiyani (Universitas Sebelas Maret, 2023)
Objective: This study aimed to determine the percentage of reproductive disorders in dairy cows at The Northern Bandung Dairy Farmer Cooperative (KPSBU Lembang) based on body condition score (BCS) and season factor and determined the distribution map.Methods: The object of this study was secondary data on dairy cows from 2019 to 2021 registered on the cooperative database. The parameters of this study were type, case percentage, risk factor, and distribution of reproductive disorders. The data were analyzed descriptively based on BCS and season factors.Results: The percentage results were presented in tables and figures after being processed using Microsoft Excel, while the distribution maps were processed using the QGIS application. The percentages of reproductive disorders in KPSBU Lembang in 2019–2021 respectively as follows: Retained placenta were 11.5%, 14.9%, and 14.4%; Dystocia were 11.5%, 12.6%, and 14.2%. Ovarian function disorders (follicular cyst and corpus luteum cyst) were 10.2%, 8.8%, and 9.9%; Endometritis was 9.3%, 9.5%, and 10.4%. Based on the distribution maps of reproductive disorders, it was known that all villages in Lembang District in 2021 had cows with reproductive disorders.Conclusions: The reproductive disorders in dairy cows at KPSBU Lembang had retained placenta, dystocia, ovarian function disorder (follicular cyst and corpus luteum cyst), and endometritis. Dystocia and retained placenta are the highest cases in KPSBU Lembang during the dry and rainy seasons. Areas that had dairy cows with unideal BCS became the highest area of each type of reproductive disorder cases.Objective: This study aimed to determine the percentage of reproductive disorders in dairy cows at The Northern Bandung Dairy Farmer Cooperative (KPSBU Lembang) based on body condition score (BCS) and season factor and determined the distribution map.Methods: The object of this study was secondary data on dairy cows from 2019 to 2021 registered on the cooperative database. The parameters of this study were type, case percentage, risk factor, and distribution of reproductive disorders. The data were analyzed descriptively based on BCS and season factors.Results: The percentage results were presented in tables and figures after being processed using Microsoft Excel, while the distribution maps were processed using the QGIS application. The percentages of reproductive disorders in KPSBU Lembang in 2019–2021 respectively as follows: Retained placenta were 11.5%, 14.9%, and 14.4%; Dystocia were 11.5%, 12.6%, and 14.2%. Ovarian function disorders (follicular cyst and corpus luteum cyst) were 10.2%, 8.8%, and 9.9%; Endometritis was 9.3%, 9.5%, and 10.4%. Based on the distribution maps of reproductive disorders, it was known that all villages in Lembang District in 2021 had cows with reproductive disorders.Conclusions: The reproductive disorders in dairy cows at KPSBU Lembang had retained placenta, dystocia, ovarian function disorder (follicular cyst and corpus luteum cyst), and endometritis. Dystocia and retained placenta are the highest cases in KPSBU Lembang during the dry and rainy seasons. Areas that had dairy cows with unideal BCS became the highest area of each type of reproductive disorder cases.